Development of Digital Standard Operating Procedures for Final Project at Faculty of Islamic Economics and Business IAIN Palangka Raya - Ahmad Kurniawan, Zulfa; Mubarok, Arif; Hakim, Sofyan (Amala Jurnal Pengabdian Kepada Masyarakat, 2022)
Universities should not only put pressure on, but also start to innovate to facilitate students, especially in terms of information and services that can help students complete their final assignments/thesis. Sometimes, students are confused with the stages of writing a thesis starting from submitting a title until the thesis is ready to be tested. Some of the problems found in the student environment related to the process of submitting the thesis are firstly the Standard Operating Procedure (SOP) for the student's thesis has not been systematically arranged, secondly the unclear requirements for thesis submission, thirdly the absence of teaching aids or tools that make it easier for students to obtain information independently, the four internal and external evaluations in order to produce SOPs that are tested both inside and outside the organizational environment. Therefore, it is deemed necessary to develop a Standard Operating Procedure (SOP) for the student's thesis which is then socialized to the academic community, especially product users. The results of this activity are the SOP Booklet for the thesis of FEBI IAIN Palangka Raya students and the installation of Banner Stands that make it easier for students to access the SOPs.